Three new species of eriophyoid mites (Acari: Prostigmata: Eriophyoidea) from Montenegro - Jočić, Ivona; Petanović, Radmila; Vidović, Biljana (Zootaxa, 2011)
Three new species of eriophyoid mites from Montenegro are described and illustrated. The first, Phytoptus alchemillae n. sp. (Phytoptidae), is found on the basic rosette of leaves of Alchemilla hoppeana (Rchb.) D. Torre, aggr. (Rosaceae). The second species, Leipothrix menthae n. sp. (Eriophyidae), is located on the undersurface of Mentha piperita L. (Lamiaceae) leaves and the third species, Aculus blagayanae n. sp. (Eriophyidae), inhabits the receptacles of the subendemic plant species, Daphne blagayana Frey. (Thymelaeaceae). All three species are vagrants, causing no visible damage to their plant host.